Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C. J.; Tomás Barberán, F. a; Espin, J. C.; López Carrasco, C.; Olivares, A.; Rey, a I. (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
The following values have no corresponding Zotero field: accession-num: 22064301
Keywords: Curculio; fat; fatty acid; iberian pig

Effect of feeding system on the growth and carcass characteristics of Iberian pigs, and the use of ultrasound to estimate yields of joints. - Daza, a; Mateos, A.; López Carrasco, C.; Rey, A.; Ovejero, I.; López-Bote, C. J. (Meat science, 2006)
Forty three-castrated male Iberian pigs of the Torbiscal line with an average initial weight of 102.27kg were used. A group of 22 pigs was fed according to the traditional way in free-range conditions with acorn and grass from November to January. Another group of 21 animals was fed 3.72kg/day of a conventional feed that contained 12.53MJME/kg, 16.21% crude protein, 4.94% fat and 6.64% of crude fiber, during the same period. Measurements of backfat thickness and Longissimus dorsi muscle area at the last rib were taken by means of a real-time ultrasound device (Kretz Technick Inc., 600 V-V2.32, Sonovet, Austria) in all pigs before slaughter. After slaughter, carcass, ham and foreleg weights and backfat and muscle area measurement from the last rib chop were recorded. The average daily gain, carcass yield, fat thickness, loin area, ham weight and proportion of hams were significantly higher (P<0.05) in the pigs fed in confinement than in those fed extensively (653.36g, 77.97%, 56.46mm, 3031mm(2), 22.26kg and 14.32% vs 501.48g, 76.94%, 51.74mm, 2673mm(2), 21.52kg and 13.79%, respectively). This paper shows the prediction equations for hams, forelegs and total hams and forelegs weights and proportions with respect to slaughter weight and live ultrasound measurements in pigs fed either extensively or in confinement. The ultrasound measurements better predicted the carcass cuts absolute amounts (R(2)=0.591-0.875) than the carcass cuts proportions (R(2)=0.23-0.40). The use of real-time ultrasound should be used with caution to predict the absolute quantities of hams and forelegs from Iberian pigs since the ultrasound measurements are only moderately accurate.
The following values have no corresponding Zotero field: accession-num: 22061368
Keywords: carcass; feeding; Growth; iberian pig; ultrasounds